SUBTANSI AGAMA DAN BANALITAS MEDIA - Wawan Setiawan; Erin Alvianita (STAINU Tasikmalaya, 2022)
The purpose of this study is to find out how to restore one's belief in the real religion, and why someone becomes bored (banality) in getting information on social media. The research method uses library research by collecting data from writings (literacy) that are related to the topics discussed, namely the substance of religion and the banality of media. The results of this study indicate that religion and the media on the one hand have something in common, namely in terms of seeking the truth. Religion seeks truth. The media is also moving in search of the truth. The difference is, if religion claims to have found the truth, the media does not say so. Religion and the media no longer need to be contradicted because both are in a condition of mutual need. The substance of religion is very necessary for its existence by the community because religion plays a role and functions to direct humans to belief, goodness, teaches and educates humans to be gentle in heart, soul, body and mind. Meanwhile, media banality is a condition when various messages and information conveyed through mass media lose their spirit and become meaningless.